Strategi Guru dalam Pembelajaran Aqidah Akhlak Di MTs Negeri 2 Balikpapan - Mahmudah, Imil; Jannah, Fathul; Basith, Abdul (Faculty of Education and Teacher Training of UINSI Samarinda, 2022)
MTs Negeri 2 Balikpapan is a school that plays an important role in learning Aqidah Akhlak which has included in the school's mission, namely